PERKEMBANGAN SANGGAR SENI TARI TOPENG MULYA BHAKTI DI DESA TAMBI - Dimas Rachmat Susilo; Didin Saripudin; Syarief Moeis (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
The main purpose of this paper is to describe the Development of Sanggar Seni Tari Topeng Mulya Bhakti in Tambi Village, Indramayu between 19832015. This paper uses the istorical method, this method consists of: heuristic, critic, interpretation and historiography. While the main topic of this paper is how was the development of Sanggar Mulya Bhakti traditional dance studio in Tambi Village, Indramayu. Mulya Bhakti was established by Mama Taham, who was born in traditional dancer family which was successfully succeeded by their ancestors. Sanggar Mulya Bhakti is one of few traditional dance studio, especially focused on traditional mask dance, that still survive in the middle of foreign culture wave. Mama Taham established the studio because he didn’t wanted to see his children grew up without knowing their native culture and trapped on globalization era. We can see his success of teaching traditional mask dance to his children nowadays because now the managers of Sanggar Mulya Bhakti are his children and Sanggar Mulya Bhakti is better, popular and well developed than before.